Mining of Cyanobacterial Genomes Indicates Natural Product Biosynthetic Gene Clusters Located in Conjugative Plasmids - Popin, Rafael Vicentini; Alvarenga, Danillo Oliveira; Castelo-Branco, Raquel; Fewer, David Peter; Sivonen, Kaarina (Frontiers in Microbiology, 2021)
Microbial natural products are compounds with unique chemical structures and diverse biological activities. Cyanobacteria commonly possess a wide range of biosynthetic gene clusters for the production of natural products. Although natural product biosynthetic gene clusters have been found in almost all cyanobacterial genomes, little attention has been given in cyanobacterial research to the partitioning of these biosynthetic pathways in chromosomes and plasmids. Cyanobacterial plasmids are believed to disperse several natural product biosynthetic gene clusters, such as toxins, by plasmids through horizontal gene transfer. Therefore, plasmids may confer the ability to produce toxins and may play a role in the evolution of diverse natural product biosynthetic gene clusters from cyanobacteria. Here, we performed an analysis of the distribution of natural product biosynthetic gene clusters in 185 genomes and mapped the presence of genes involved in conjugation in plasmids. The 185 analyzed genomes revealed 1817 natural products biosynthetic gene clusters. Individual genomes contained one to 42 biosynthetic pathways (mean 8), 95% of which were present in chromosomes and the remaining 5% in plasmids. Twelve percent of the 424 analyzed cyanobacterial plasmids contained homologs of genes involved in conjugation and natural product biosynthetic pathways. Among the biosynthetic pathways in plasmids, manual curation identified those for the production of aeruginosin, anabaenopeptin, ambiguine, cryptophycin, hassallidin, geosmin, and microcystin. These compounds are known toxins, protease inhibitors, odorous compounds, antimicrobials, and antitumorals. The present study provides in silico evidence using genome mining that plasmids may be involved in the distribution of natural product biosynthetic gene clusters in cyanobacteria. Consequently, cyanobacterial plasmids have importance in the context of biotechnology, water management, and public health risk assessment. Future research should explore in vivo conjugation and the end products of natural product biosynthetic gene clusters in plasmids via chemical analyses.